2002
DOI: 10.4319/lo.2002.47.4.1165
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological controls of gas exchange at a small English lake

Abstract: The relationships between gas transfer velocity, k 600 , wind speed, wind direction, rainfall, and relative humidity were examined using measurements of SF 6 evasion from Coatenhill Reservoir, a small (0.017 km 2 ), shallow (1.9 Ϯ 0.1 m), man-made lake in northeast England characterized by predominantly low to intermediate wind speeds ϳ1-10 m s Ϫ1 . A graphical method was used to estimate the wind speed at a standard height of 10 m, U 10 , from wind speed measurements at 2 m and 3.8 m. Derived values of U 10 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 47 publications
(119 reference statements)
1
24
1
Order By: Relevance
“…However, systematic measurements of these properties remain to be made. Also, there have only been a few gas exchange experiments in the natural environment where rain-forcing has been considered [Cole and Caraco, 1998;Frost and Upstill-Goddard, 2002], and no systematic studies have been conducted. The mechanisms behind rain-induced gas exchange, and the interaction of rain-and wind-generated waves and turbulence, should be examined in greater depth.…”
Section: Discussionmentioning
confidence: 99%
“…However, systematic measurements of these properties remain to be made. Also, there have only been a few gas exchange experiments in the natural environment where rain-forcing has been considered [Cole and Caraco, 1998;Frost and Upstill-Goddard, 2002], and no systematic studies have been conducted. The mechanisms behind rain-induced gas exchange, and the interaction of rain-and wind-generated waves and turbulence, should be examined in greater depth.…”
Section: Discussionmentioning
confidence: 99%
“…However, the existence of a unique and universal wind-k relationship for all systems is highly questionable given that for any wind speed, its effect on gas exchange is unlikely to be the same in the ocean and, for example, in a small kettle lake. Moreover, many studies have shown that other factors will affect k, such as wind fetch (Frost and Upstill-Goddard 2002;Borges et al 2004;Guérin et al 2007), tidal currents (Borges et al 2004;Zappa et al 2007), rainfall (Ho et al 1997(Ho et al , 2007, microscale breaking waves (Zappa et al 2004), thermal convection (Schladow et al 2002;Eugster et al 2003), organic matter or suspended matter (Abril et al 2009;Calleja et al 2009), and surfactants (Frew et al 1990;McKenna and McGillis 2004).…”
mentioning
confidence: 99%
“…While this is particularly obvious for marine systems, inland waters have recently been shown to have a larger-than-expected role in this regard (Cole et al 2007). However, the physical processes modulating gas exchange with the atmosphere are complex and are currently modeled only with great uncertainty (Frost and Upstill-Goddard 2002;Zappa et al 2007). Consequently, accurate carbon emission estimations are difficult to achieve.…”
mentioning
confidence: 99%
“…Broeker and Peng, 1982;Mackay and Yeun, 1983;Liss and Merlivat, 1986;Wanninkhof, 1992 al ., 1993;Wanninkhof and McGillis, 1999;Cole and Caraco, 1998;Frost and Upstill-Goddard, 2002). All quantitative expressions predict enhanced air/water exchange with an increase in windspeed.…”
Section: The Diffusivity Of Gaseous Mercury In Watermentioning
confidence: 99%